INOVASI PROMOSI KERAJINAN “SANDAL BANDOL” SEBAGAI OLEH-OLEH UNIK UNTUK PENGUNJUNG HOTEL DI KABUPATEN BANYUMAS MELALUI E-KATALOG - Imam Tahyudin; Bayu Ibnu Syafiq; Bagus Budi Santoso (Universitas Sanata Dharma, 2021)
Promotional innovation using e-catalogs is one of the efforts to increase the number of bandol sandal handicraft sale. The bandol sandal e-catalog is used to focus on promotions for hotel visitors in Banyumas district. The steps taken include the selection of quality sandal products and attractive designs through a design competition. Then the selected product is made a catalog and e-catalog. Through cooperation with hotel management, it is expected to be able to target hotel customers in Banyumas district. This service activity succeeded in selecting attractive and quality bandol sandals, catalogs and e-catalogs.